137k views
4 votes
Let p(x)=90/9+50e^-x What is p(3)

User SnK
by
5.5k points

2 Answers

4 votes

Answer:

p (3) = 7.83

Explanation:

We are given the following expression and we are to evaluate it given that the value of
p = 3:


p ( x ) = \frac { 9 0 } { 9 + 5 0 e^ { - x } }

Substituting the given value of
p to get:


p ( 3 ) = \frac { 9 0 } { 9 + 5 0 e^ { - 3 } }


p ( 3 ) = \frac { 9 0 } { 11.489 }


p ( 3 ) = 7.83

User Madhumitha
by
4.5k points
1 vote

Answer:

If it is
p(x)=(90)/((9+50e^(-x))), then:
p(3)=7.83

If it is
p(x)=(90)/(9)+50e^(-x), then:
p(3)=12.48

Explanation:

To solve this exercise you must substiute x=3 into the expression given in the problem.

1) If the expression is
p(x)=(90)/((9+50e^(-x))), you obtain:


p(3)=(90)/((9+50e^(-(3))))


p(3)=7.83

2) If the expression is
p(x)=(90)/(9)+50e^(-x), you obtain:


p(3)=(90)/(9)+50e^(-(3))\\p(3)=12.48

User Bolizhou
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.